Design of Purse Seine Fishing Vessel Modification at Bulukumba South Sulawesi Province - Yopi Novita; Budi Harscahyo Iskandar; Mohammad Imron; Hery Sutrawan Nurdin (Jurnal Perikanan dan Kelautan, 2016)
Bulukumba regency is well known by international community as the areas of phinisi shipbuilding. Shipbuilding procces in Bulukumba Regency made a traditional dockyard system. The skills used the experience from generation to generation. Limited investment was one of the problems, so that the construction of the ship in Bulukumba the craftsman forced to modification the cargo ship to be the fishing vessel. The aim of the research is comparing the design character of the purse seiner modification toward cargo ship and purse seiner in Bulukumba. This research done with make a measurement, observationand direct interview. Calculation and ship drawing methods used the naval architecture method. Data analyzed a numeric, comparative and descriptive set. Result of the study showed a principal dimension of purse seiner modification tend to have the same value with cargo ship in Bulukumba. Value of principal dimension of purse seiner modification is smaller than purse seiner in Bulukumba. Freeboard of purse seiner modification is high. The hull of purse seiner modification have a round bottom type, so it can reduce resistance value. Character of coefficient of fineness purse seiner modification tend to have the same value with cargo ship. The coefiicient of fineness value of purse seiner modification smaller than of purse seiner in Bulukumba.